Women post menopause: assessment of quality of life and socio-demographic correlates - Raj, Purnima; Deshmukh, Namita; Borkar, Avinash (International Journal of Basic & Clinical Pharmacology, 2019)
Background: Menopause can have psychological, physical, and vasomotor symptoms along with sexual dysfunction, Current health care model fail to recognize that these symptoms profoundly affect a woman’s personal and social functioning and ultimately her quality of life. Hence, this study aims to assess the Quality of life of post-menopausal women and finding out socio-demographic factors affecting quality of life. Methods: A cross-sectional study in an urban slum area was undertaken and 105 females between 45-65 years of age were interviewed using menopause-specific quality of life (MENQOL) questionnaire. Results: The mean age of these study participants was 54.13±4.05 (45-62) years. Out of 105 post-menopausal women included in the study, 20% were illiterate, 26.7% had completed education up to Secondary school level. Total MENQOL scores ranged from 62-148 and total mean score was 101.3±23.44. Conclusions: Menopause affected not only physical health of a woman but also affects psychosocial aspect of life and this was well evident from the present study where MENQOL scores were higher indicating poor quality of life after menopause. Ageing, lower education, lower socio-economic status, unemployment and no spouse support were contributing to the poor quality of life.